Sky Jack! - Vicary, Tim (Nxb. Đồng Nai, 2009)
When a large plane is hijacked, the Prime Minister looks at the list of passengers and suddenly becomes very, very frightened. There is a name on the list that the Prime Minister knows very well - too well. There is someone on that plane who will soon be dead - if the hijackers can find out who he is! And there isn't much time. One man lies dead on the runway. In a few minutes the hijackers will use their guns again. And the Prime Minister knows who they are going to kill.